1995
DOI: 10.1038/sj.npp.1380290
|View full text |Cite
|
Sign up to set email alerts
|

5-HT1D Receptors Regulate 5-HT Release in the Rat Raphe Nuclei

Abstract: The aim of the present study was to characterize the pharmacological profile of 5-hydroxytryptamine (5-HT) receptors modulating 5-HT release in the mesencephalic raphe region. In a first series of experiments, differential normal pulse voltammetry and nafion-coated electrodes were used to measure extracellular 5-HT in the dorsal 5-carboxy-amiditryptamine (5-CT) and the 5-HTrnno agonist sumatriptan (1-1,000 nM) induced a concentration-dependent inhibition of the electrically evoked release of [3H}5-HT from prel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1995
1995
1999
1999

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The rat is not generally held to have functional 5-HTlD receptors, although mRNA for the rat homologue of the 5-HTID, receptor is found in the DRN (Hamblin et al, 1992) and it has been tentatively suggested that there may be functional 5-HTlD receptors in the rat DRN (Pineyro et al, 1994). However these conclusions were largely based on the use of mianserin as a 5-HTID antagonist, a drug with only modest selectivity over 5-HTlB receptors (Hoyer et al, 1994).…”
Section: Pyridine)mentioning
confidence: 99%
“…The rat is not generally held to have functional 5-HTlD receptors, although mRNA for the rat homologue of the 5-HTID, receptor is found in the DRN (Hamblin et al, 1992) and it has been tentatively suggested that there may be functional 5-HTlD receptors in the rat DRN (Pineyro et al, 1994). However these conclusions were largely based on the use of mianserin as a 5-HTID antagonist, a drug with only modest selectivity over 5-HTlB receptors (Hoyer et al, 1994).…”
Section: Pyridine)mentioning
confidence: 99%
“…Seventh, for inverse agonist actions to be detected, the receptor must be present in a constitutively active state and, ideally; endogenous agonist(s) should not be present. However, in vivo, 5-HT is spontaneously released both at the dendritic and terminal level (Piñeyro et al 1995). Indeed, basal dialysate levels of 5-HT are reliably measurable, suggesting that 5-HT is available to pre-and postsynaptic receptors ).…”
Section: General Discussion: Absence Of Inverse Agonist Actions In Vivomentioning
confidence: 99%
“…The 5-HT 1A , 5-HT 1B , and 5-HT 1D receptors are of particular interest inasmuch as they are localized both postsynaptically to serotonergic neurones as well as presynaptically, as inhibitory autoreceptors on their dendrites (5-HT 1A and a minor population of 5-HT 1B/1D sites) and terminals (5-HT 1B sites) (Piñeyro et al 1995;Starkey and Skingle 1994). It might, thus, be hypothesized that inverse agonist actions at 5-HT 1A , 5-HT 1B , and/or 5-HT 1D autoreceptors may facilitate serotonergic transmission (Gaster et al 1998;Moret and Briley 1993;Roberts et al 1997).…”
Section: Experimental Strategy: Characterization Of Potential Inversementioning
confidence: 99%
“…24 " 26 Indeed, in vitro administration of sumatriptan, a 5-HT 1D agonist, induced inhibition of electrically evoked release of 5-HT from rat brain raphe slices. 25 Consequently, it could be assumed that chronic administration is associated with rapid decrease in 5-HT tone and thus an improvement in obsessive-compulsive symptoms. 2 7 Sumatriptan is an antimigraine agent whose pharmacological effect appears to be related to the 5-HT 1D receptors and is approximately 5 times less potent at 5-HT 1B receptors and 20 times less potent at 5-HT 1A receptors, having only a minor affinity at 5-HT 1E receptors.…”
Section: Pharmacological Challenges and Neuroendocrine Studiesmentioning
confidence: 99%